2023
DOI: 10.3390/mi14020406
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of a Screw Centrifugal Blood Pump Based on Random Forest and Multi-Objective Gray Wolf Optimization Algorithm

Abstract: The centrifugal blood pump is a commonly used ventricular assist device. It can replace part of the heart function, pumping blood throughout the body in order to maintain normal function. However, the high shear stress caused by the impeller rotating at high speeds can lead to hemolysis and, as a consequence, to stroke and other syndromes. Therefore, reducing the hemolysis level while ensuring adequate pressure generation is key to the optimization of centrifugal blood pumps. In this study, a screw centrifugal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…Recent studies have shown that metaheuristic algorithms perform well in solving high-dimensional optimization problems. Particle Swarm Optimization (PSO) [1], Gray Wolf Optimizer Algorithm [2], Genetic Algorithm [3], Differential Evolution Algorithm [4], Ant Colony Algorithm [5], Artificial Bee Colony Algorithm [6], Simulated Annealing Algorithm [7] are the most known and widely used stateof-the-art metaheuristic algorithms. PSO algorithm seems to be preferred more than other algorithms due to its ease of use, ability to search for the global optimum and higher convergence rate [8][9].…”
Section: Related Workmentioning
confidence: 99%
“…Recent studies have shown that metaheuristic algorithms perform well in solving high-dimensional optimization problems. Particle Swarm Optimization (PSO) [1], Gray Wolf Optimizer Algorithm [2], Genetic Algorithm [3], Differential Evolution Algorithm [4], Ant Colony Algorithm [5], Artificial Bee Colony Algorithm [6], Simulated Annealing Algorithm [7] are the most known and widely used stateof-the-art metaheuristic algorithms. PSO algorithm seems to be preferred more than other algorithms due to its ease of use, ability to search for the global optimum and higher convergence rate [8][9].…”
Section: Related Workmentioning
confidence: 99%
“…According to the theory of fluid mechanics, the shear stress between a solid and a liquid is greater than that between two liquids under the same conditions [6]. Therefore, the maximum shear stress is usually distributed on the wall surface where the blood comes into contact with the pump body.…”
Section: Wall Shear Stress Distribution Of Blood Pumpsmentioning
confidence: 99%